(untitled) (Research, Society and Development, 2022)
The objective was to evaluate the antiparasitic effect of different dosages of the alcoholic extract of propolis in the control of verminosis in sheep. Thirty-two Santa Inês sheep were used in a randomized complete block design with four treatments and eight replicates. The treatments were: 10 mL of water; 10 mL of alcohol 70%; 5 mL of propolis alcoholic extract (PAE) 30%; and 10 mL of PAE 30%. The treatments were administered orally, in a single dose. The effects of the treatments were evaluated by counting eggs per gram of faeces (EPG) for days 1; 3; 7 and 21 after administration. Oral administration of 10 mL of water or 10 mL of alcohol 70% had no effect on EPG reduction. The use of 5 mL of PAE 30% reduced EPG on days 3 and 7, reducing its efficacy on day 21, while the use of 10 mL of PAE 30% reduced EPG on all evaluated days. Thus, oral administration, in a single dose, of 10 mL of propolis alcoholic extract 30%, effectively reduced the number of EPG demonstrating antiparasitic effect and can be used in the control of verminoses as an alternative method to chemical products synthetic.